The Importance of Iron, Copper, Zinc, and Magnesium Dyshomeostasis in terms of Alzheimer’s Disease and Possible Mechanisms - Esra Tekin; Ayşegül Küçük; Mustafa Arslan (Gazi Medical Journal)
Alzheimer’s disease (AD) affects many people around the world, and its incidence is increasing. In addition to the amyloid cascade hypothesis, different mechanisms are discussed for AD, which has no definitive treatment. Studies have shown that the levels of metal cations such as iron, copper, zinc, and magnesium vary and their metabolism are impaired in patients with AD. Metal cation dyshomeostasis is believed to be one of the mechanisms that contribute to the development of AD. In this review, we aimed to evaluate various metal cations in terms of AD.